Effect of P fertilizers use on rice (Oryza sativa) productivity in Southern Province of Rwanda, Rwasave marshland. - HIRWA, Hubert (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The present study aimed at evaluating the effect of P fertilizers on rice productivity in Rwandan marshlands. It was conducted in Rwasave marshland. A Randomized Complete Block Design (RCBD) experiment comprised four P treatments [T1 as 0 kg (control), T2: 30kg, T3: 60kg, T4: 90kg of P2O5] replicated four times and Yunkeng was the test rice variety.  The soil samples were randomly collected at 0-30cm depth and various chemical and physical analyses conducted.  The results revealed the significant difference (p<0.05) among treatments for available P. The laboratory results were pHH2O of 5.37, pHKCl of 4.13 and available P (Bray I) of 4.03ppm. The P2O5 had significant (p<0.05) effect on grain yield and yield components and increased the plant height (109.0 cm), tillering, 241 filled grains/panicle, empty grains/panicle, 1000grains weight (50.6gm), and panicle numbers. Tillering activity was the growth parameter that affected most significantly the grain yield. P rich fertilizer (P2O5) applied at 90kg P ha-1 produced the highest grain yield (7.69t/ha) against the lowest grain yield (3.31t/ha) of control. This study revealed that the supply of P fertilizers for some farmers did not meet the rice requirements. The response of rice to P application depends on available soil P levels. It is necessary to apply P fertilizers with adequate doses and at the right time in order to maintain the stability of available P in the soil.